다차원적 빈곤과 아동의 학업 성취 : 빈곤가정 아동을 중심으로 - 김희정; 김윤태 (사회적질연구, 4(1), 2020)
이 연구의 목적은 아동의 다차원적 빈곤이 학업 성취에 미치는 경로와 영향력을 분석하는 것이다. 분석은 한국복지패널의 가구용·가구원용 자료와 아동부가조사(4, 7, 10차)를 활용했다. 먼저 퍼지셋 질적분석방법(Fs/QCA)을 통해 아동 가구의 다차원적 빈곤율을 산출하여 독립변수로 활용하였고, 아동의 학업성취에 미치는 경로에서 아동 및 부모 요인을 투입하여 구조 모형으로 설정하였다. 주요 분석 결과는다음과 같다. 첫째, 다차원적 빈곤 수준이 높아질수록 부모의 지도 감독 및 교육 참여 수준은 낮아졌고, 특히 자녀의 연령이 어릴수록 부(-)적 영향력은 커졌다. 둘째, 비교적 연령이 낮은 초등학생과 중학생은 부모의 교육적 관심이 커질수록 학업 성취 수준이 높아졌다. 이는 자녀의 연령이 어릴수록 가족 자원(family resources)이 학업 성취에 미치는 영향력이 커진다는 선행연구의 결과와 유사하다. 셋째, 부모 요인이 자녀의 심리 내적 상태(자아 존중감, 주의 집중 등)에 미치는 영향력은 연령이 어릴수록 커지는 반면, 아동의 심리내적 상태가 학업 성취에 미치는 영향력은 연령이 높아질수록 증가하였다. 마지막으로 다차원적 빈곤과 아동의 학업 성취 간 경로에서 아동 요인은 부분 매개하는 것으로, 부모 요인은완전 매개하는 것으로 확인되었다. 분석 결과를 종합하면 아동 가구의 다차원적 빈곤 수준이 높을수록아동의 학업 성취에 부정적인 영향을 미쳤으나, 아동의 심리 내적 요인과 부모 역할에 따라 학업 성취수준은 달리지는 것으로 해석된다. The purpose of this study is to analyze the degree of influence that children’s multidimensional poverty exerts on their academic achievements. For the analysis, the Korea Welfare Panel Study (KOWEPS)’s data on households, household members, and its additional children surveys (4th, 7th and 10th surveys) were used. First, the multidimensional poverty rate of households with children was calculated through the fuzzy-set qualitative analysis (fs/QCA) methodology and then used as an independent variable. Next, regarding the potential impact on children's academic achievements, the child and parent factors were put into the structural model. The main results are as follows: First, as the level of multidimensional poverty got higher, the parental supervision and education participation levels became lower. In particular, the younger the child was, the greater the negative influence became. Second, as for the relatively young kids like elementary and middle school students, their academic achievement levels got higher when their parents grew more interested in their education. This is similar to the results of previous studies that showed the younger the age of the child was, the greater the influence of family resources on their academic achievements became. Third, the parent factors had greater influences on the internal status of children’s psychology, such as self-esteem and attention span, when the children were younger. However, the child factors—or the internal status of children’s psychology—became more influential as the children grew older. Lastly, as for the relationship between multidimensional poverty and children’s academic achievement, the child factor is found to be a partially mediating factor while the parent factor is a fully mediating one. The analysis shows that when households had higher levels of multidimensional poverty, this had a more negative effect on children’s academic achievements. However, this can also be interpreted that children’s academic achievements heavily depend on the parents’ interest and on their internal psychological factors. KCI Citation Count: 4